Pengembangan Sistem Informasi Manajemen Tesis (Studi Kasus: Program Studi Magister Administrasi Bisnis Fakultas Ilmu Administrasi UB) - Afif Nandya Saputra; Satrio Agung Wicaksono; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Master of Business Administration is a program of masgiter study at Faculty of Administrative Sciences Universitas Brawijaya Malang. Currently every stage of thesis work is using physical forms that must be filled by students. The physical form is changed hands or forwarded to the parties involved in the thesis workflow for approval or signature. The use of physically transferred or forwarded forms for approval may slow the flow of thesis work. This happens because the physical form is submitted and checked manually. Based on the mentioned problems, so the solution can be given is to develop a thesis management information system that serves to overcome the problem due to the use of the physical form. The result of this research are 52 functional requirement and 1 non functional requirement. From Black-box testing, 52 functional requirements have been tested and 100% valid. Compatibility testing that has been done, resulting the system can run smoothly on the computer web browser and mobile device web browser except on the web browser IE 9 and web browser BlackBerry 7.1.